Cat Scabies at The Animal Health Clinic of Salatiga Agriculture Service on August to November 2020 - Meta Iqomah; Nuraini Suwarno; Puji Yuliani (Journal of Parasite Science (JoPS), 2020)
Scabies is a disease caused mites and zoonotic. Scabies in cats can be caused the mites Sarcoptes scabiei and Notoedres cati. This Study aims to investigate the causes of skin disease and treatment of cats that come to the animal health clinic of Salatiga City Agriculture Service with clinical symptoms similar to scabies. Data collection was carried out from August to November 2020. Confirmation of the diagnosis was done by skin scraping the scab of the earlobe and/ or fingers and observed under a microscope with 100x magnification. The sticking of skin scrap uses liquid paraffin. The results of the investigation showed that a number of nine cats were positive for scabies with the cause mite is Sarcoptes scabiei. Treatment is done by administering ivermectin injection at a dose of 400 mcg/kg body weight and diphenhydramine 1 mg/kg body weight. Of the nine cats, there were three cats that received treatment repetitions up to two times. Without repeated skin scraping, the nine cats recovered with relief of clinical symptoms after treatment.